Redefining Infarction Size for Small-Vessel Occlusion in Acute Ischemic Stroke: A Retrospective Case-Control Study - Yen-Chu Huang; Hsu-Huei Weng; Leng-Chieh Lin; Jiann-Der Lee; Jen-Tsung Yang; Yuan-Hsiung Tsai; Chao-Hui Chen (MDPI AG, 2024)
Background/Objectives: Small-vessel occlusion, previously referred to as lacunar infarcts, accounts for approximately one-third of all ischemic strokes, using an axial diameter of less than 20 mm on diffusion-weighted imaging. However, this threshold may not adequately differentiate small-vessel occlusion from other pathologies, such as branch atheromatous disease (BAD) and embolism. This study aimed to assess the clinical significance and pathological implications of acute small subcortical infarctions (SSIs) based on infarct diameter. Methods: We conducted a retrospective case-control study using data from stroke patients recorded between 2016 and 2021 of the Stroke Registry in Chang Gung Healthcare System. Patients with acute SSIs in penetrating artery territories were included. Key variables such as patient demographics, stroke severity, and medical history were collected. Infarcts were categorized based on size, and the presence of early neurological deterioration (END) and favorable functional outcomes were assessed. Results: Among the 855 patients with acute SSIs, the median age was 70 years and the median National Institutes of Health Stroke Scale (NIHSS) score at arrival was four. END occurred in 97 patients (11.3%). Those who experienced END were significantly less likely to achieve a favorable functional outcome compared to those who did not (18.6% vs. 59.9%, p < 0.001). The incidence of END increased progressively with infarct sizes of 15 mm or larger, with the optimal threshold for predicting END identified as 15.5 mm and for BAD, it was 12.1 mm. A multiple logistic regression analysis revealed that motor tract involvement [adjusted odds ratio (aOR) 2.3; 95% confidence interval (CI) 1.1-4.7], an initial heart rate greater than 90 beats per minute (aOR 2.3; 95% CI 1.2-4.3), and a larger infarct size (15 mm to less than 20 mm vs. 10 mm to less than 15 mm; aOR 3.0; 95% CI 1.4-6.3) were significantly associated with END. Conclusions: Our findings suggest that setting the upper limit for small-vessel occlusion at 15 mm would be more effective in distinguishing it from BAD. However, these findings should be interpreted in the context of the retrospective design and study population. Further multi-center research utilizing high-resolution vessel wall imaging is necessary to refine this threshold and enhance diagnostic accuracy.